Antagonistic potential of endophytic bacteria from tomato seedlings - Milena Campos de Oliveira Alencar Viana; Júlia Karoline Ferreira Moura; Maria Gabriela Gomes de Lima; Igor Daniel Alves Ribeiro; Luciane Maria Pereira Passaglia; Marcos Cabral de Vasconcellos Barreto; Pedro Roberto Almeida Viégas; Regina Helena Marino (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the antagonistic potential of endophytic bacteria isolated from 'Cereja Vermelho', 'Rasteiro Rio Grande', and 'Chapolin' tomato seedlings against the ALT23 Alternaria sp. fungus. Of the 23 endophytic isolates obtained, 12 were selected due to their greater effect on the mycelial growth of ALT23. Antagonism was tested in a completely randomized design, with 13 treatments (ALT23 and 12 isolates), with four replicates. The selected endophytic bacteria inhibited from 29.8 to 64.2% of the mycelial diameter and from 33.7 to 72.4% of the growth rate of ALT23.